Eksplicitnost pri prevajanju slovenskih narodnih jedi - Šumrada, Simona (Jezik in slovstvo, 2009)
The purpose of the article is to shed light on the problem of the presentation of Slovene cultural realities in tourism-related texts and to establish the need for greater professionalism. In an analysis of French and English translations of Slovene national dishes in menus of Slovene restaurants and in print and Internet publications about Slovenia it is evident that less explicit translation approaches prevail, such as approximate translation, literal translation and description. Furthermore, as many as seventeen various translation solutions appear for the same dish. All of this contributes to a loss of identity and recognition of national dishes. In comparable texts from foreign sources these kinds of cultural realities are presented more explicitly, most frequently in the form of a pairing of the cited form along with a description, which enables both recognition of the dish and understanding. In the article we will attempt to indicate certain key reasons why we can expect more explicit and unified translation solutions in the translations of texts of an informative nature, such as the above mentioned tourism-related texts.
Keywords: angleščina; English; francoščina; French; kulinarika; prevajalski postopki; prevajanje; primerjalne študije; Slovene; slovenske narodne jedi; slovenščina; translation